Difficulty accessing condoms because of the COVID-19 pandemic reported by gay, bisexual and other men who have sex with men in the UK: findings from a large, cross-sectional, online survey. (July 2023) - Brown, Jack RG; Reid, David; Howarth, Alison R; Mohammed, Hamish; Saunders, John; Pulford, Caisey V; Ogaz, Dana; Hughes, Gwenda; Mercer, Catherine H
Background: COVID-19 restrictions severely reduced face-to-face sexual health services, an important access point for condoms. We examine whether gay, bisexual and other men who have sex with men (GBMSM) in the UK had difficulty accessing condoms during the first year of the pandemic, and if so, which groups were most affected. Methods: Questions about difficulty accessing condoms were asked as part of a short, online cross-sectional survey of GBMSM undertaken November/December 2021, recruited via social media and Grindr. Eligible participants were UK-resident GBMSM (cis/trans/gender-diverse person assigned male at birth [AMAB]), aged ≥16 years who were sexually active (reported sex with men in the last year). Multivariable logistic regression was used to examine if and how reporting this outcome varied by key sociodemographic, health and behavioural factors independent of the potential confounding effect of numbers of new male sex partners. Results: Of all participants ( N = 1039), 7.4% ( n = 77) reported difficulty accessing condoms due to the pandemic. This was higher among younger GBMSM (aged 16–29 years vs. ≥45; 12.8% vs. 4.9%; aOR: 2.78); trans/gender-diverse AMAB participants (vs. cis gender males; 24.4% vs. 6.6%; aOR = 4.86); bisexually-identifying participants (vs. gay-identifying; 11.1% vs. 6.5%; aOR = 1.78); and those without degree level education (vs. having a degree; 9.8% vs. 5.6%; aOR = 2.01). Conclusions: A minority of sexually active GBMSM reported difficulty accessing condoms because of the pandemic, however, this was more common amongst those who already experience a disproportionate burden of poor sexual health. Interventions are needed to address these inequalities in accessing this important primary STI/HIV prevention measure.